Anodal excitation in the Hodgkin-Huxley nerve model. - Fitzhugh, R (1976)
Computations show that cathodal rheobase increases with temperature from 0 degrees C to 30 degrees C. Anodal rheobase (stimulation at the end of an indefinitely long anodal pulse) also increases with temperature, but goes to infinity at a critical temperature 17.13 degrees C, above which such excitation is impossible. For a stimulus consisting of any step change of current from I0 to I1, a threshold curve of I1 is plotted against I0. As the temperature increases, this curve rises. Its intersection with the horizontal axis, which determines the anodal rheobase, goes to infinity at the critical temperature. This phenomenon is caused by the saturation of the variables m, h, n for strongly hyperpolarized potentials, combined with the relative speeding up of the inhibitory process with increasing temperature. The threshold charge Q in an instantaneous anodal current pulse (of zero duration) goes to infinity at the same temperature, with a similar explanation in terms of threshold curves in the I1 vs. Q plane. The fact that the critical temperature for both cases is the same is generalized by the conjecture that for any anodal current waveform whatever, as its amplitude approaches infinity, the trajectory in the phase space following its cessation approaches the same limiting trajectory. This limiting trajectory changes from suprathreshold to subthreshold at the critical temperature.